MODERN IN TEACHING THE SCIENCES OF ENGINEERING GRAPHICS METHODOLOGY OF USING GRAPHIC PROGRAMS - Yo’ldshev Bilol Iqboljon O’g’li (American Journals, 2023)
In this article, the science of engineering graphics of computer graphics role in education and training of modern automated design programs the improved method is reflected.
Keywords: CAD, natural processing, artificial processing, computer graphics, engineering graphics.